A Comparative Analysis of Outcomes Between Two Different Intramuscular Progesterone Preparations in Women Undergoing Frozen Embryo Transfer Cycles - S Seshadri; R Odia; O Ozturk; S Wiam; A AlChami; XV Gonzalez; S Salim; W Saab; P Serha (JRI, 2022)
Background: The purpose of the current study was to assess if luteal support with intramuscular (IM) 17 alpha-hydroxyprogesterone caproate (17-OHPC) (Lentogest, IBSA, Italy) improves the pregnancy outcome in comparison to natural intramuscu-lar progesterone (Prontogest, AMSA, Italy) when administered to recipients in a frozen embryo transfer cycle. Methods: A retrospective comparative study was performed to evaluate outcomes between two different intramuscular regimens used for luteal support in frozen embryo transfer cycles in patients underwent autologous in vitro fertilization (IVF) cycles (896 IVF cycles) and intracytoplasmic sperm injection (ICSI) who had a blastocyst transfer from February 2014 to March 2017 at the Centre for Reproductive and Genetic Health (CRGH) in London. Results: The live birth rates were significantly lower for the IM natural progesterone group when compared to 17-OHPC group (41.8% vs. 50.9%, adjusted OR of 0.63 (0.31-0.91)). The miscarriage rates were significantly lower in the 17-OHPC group compared to the IM natural progesterone group (14.5% vs. 19.2%, OR of 1.5, 95% CI of 1.13-2.11). The gestational age at birth and birth weight were similar in both groups (p=0.297 and p=0.966, respectively). Conclusion: It is known that both intramuscular and vaginal progesterone preparations are the standard of care for luteal phase support in women having frozen embryo transfer cycles. However, there is no clear scientific consensus regarding the optimal luteal support. In this study, it was revealed that live birth rates are significantly higher in women who received artificial progesterone compared to women who received natural progesterone in frozen embryo transfer cycles.